The Muhadatsah Program with Communicative and Contextual Approaches in Enhancing Students’ Speaking Skills (Kalam) at Ma'had Tahfidz Al-Qur'an Al-Amien Madura - Islam, Nur Izzatul; Ahmed, Bakri Mohammad Bkheet; Chamidah, Dewi; Bahri, Muhammad Riza Salsabila (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2025)
The Muhadatsah program is a key component of Arabic language instruction, delivered through dialogues that emphasize interactive, two-way communication between speakers and listeners. Communicative and contextual approaches are central to this method, aiming to develop students’ speaking skills (maharah kalam) for effective, real-life communication rather than focusing solely on grammar or vocabulary memorization. This study aims to: (1) describe the implementation of the Muhadatsah program using communicative and contextual approaches at Ma'had Tahfidz Al-Qur'an Al-Amien; (2) identify challenges and solutions in its implementation; and (3) analyze the program’s contribution to students' speaking proficiency. A qualitative descriptive approach was employed, focusing on the